Mechanistic Studies of Antibiotic Adjuvants Reducing Kidney's Bacterial Loads upon Systemic Monotherapy - Fadia Zaknoon; Ohad Meir; Amram Mor (MDPI AG, 2021)
We describe the design and attributes of a linear pentapeptide-like derivative (C14(<semantics>ω</semantics>5)OOc10O) screened for its ability to elicit bactericidal competences of plasma constituents against Gram-negative bacteria (GNB). In simpler culture media, the lipopeptide revealed high aptitudes to sensitize resilient GNB to hydrophobic and/or efflux-substrate antibiotics, whereas in their absence, C14(<semantics>ω</semantics>5)OOc10O only briefly delayed bacterial proliferation. Instead, at low micromolar concentrations, the lipopeptide has rapidly lowered bacterial proton and ATP levels, although significantly less than upon treatment with its bactericidal analog. Mechanistic studies support a two-step scenario providing a plausible explanation for the lipopeptide's biological outcomes against GNB: initially, C14(<semantics>ω</semantics>5)OOc10O permeabilizes the outer membrane similarly to polymyxin B, albeit in a manner not necessitating as much LPS-binding affinity. Subsequently, C14(<semantics>ω</semantics>5)OOc10O would interact with the inner membrane gently yet intensively enough to restrain membrane-protein functions such as drug efflux and/or ATP generation, while averting the harsher inner membrane perturbations that mediate the fatal outcome associated with bactericidal peers. Preliminary in vivo studies where skin wound infections were introduced in mice, revealed a significant efficacy in affecting bacterial viability upon topical treatment with creams containing C14(<semantics>ω</semantics>5)OOc10O, whereas synergistic combination therapies were able to secure the pathogen's eradication. Further, capitalizing on the finding that C14(<semantics>ω</semantics>5)OOc10O plasma-potentiating concentrations were attainable in mice blood at sub-maximal tolerated doses, we used a urinary tract infection model to acquire evidence for the lipopeptide's systemic capacity to reduce the kidney's bacterial loads. Collectively, the data establish the role of C14(<semantics>ω</semantics>5)OOc10O as a compelling antibacterial potentiator and suggest its drug-like potential.